BODIES OF KNOWLEDGE;BODIES OF KNOWLEDGE ([S.l.] : AFRICAN SUN MEDIA, 2021)
Spanning the countries of South Africa, Swaziland, and Ghana, this collection of work brings into focus child and youth experience together as a collage of anthropology, creative writing, poetry, and the fine arts.
eBooks on EBSCOhost
Keywords: Terminally ill children -- Africa -- Personal narratives; Abused children -- Africa -- Personal narratives; Phenomenology; Well-being -- Health aspects -- Africa; Well-being -- Africa -- Religious aspects; Enfants malades en phase terminale -- Afrique -- Récits personnels; Phénoménologie.; Bien-être -- Afrique -- Aspect religieux; phenomenology; Abused children; Phenomenology; Terminally ill children; Well-being -- Religious aspects; Africa; Personal narratives